The Contribution of Islamic Scholars in Addressing Earthquake and Tsunami (The Study of Malay Minangkabau Manuscripts) - Firdaus Firdaus (Insaniyat : Journal of Islam and Humanities, 2017)
The  aim  of  this  paper  is  to  examine  the  contribution  of  Minangkabau  muslim  scholars  in  responding to  the  earthquake  and  tsunami  based  on  the  manuscript  of  earthquake  takwil.  The  manuscript  of  the earthquake  takwil  becomes  the  window  to  see  how  great  the  contribution  of  muslim  scholars  in addressing the natural phenomenon in Minangkabau particularly earthquake and tsunami. In term of natural disaster, this study has been interestingly discussed since the deadly earthquake and tsunami of 26  December  2004  hit Aceh  which  killed  more  than  280.000  people.  People  become  traumatized  and feared especially the people who live in the areas affected by the earthquake and tsunami. In addition, Indonesia  is  prone  to  earthquakes  and  tsunamis  because  it  lies  on  the  “Ring  of  Fire”—the  line  of frequent quakes and volcanic eruptions that circles virtually the entire Pacific rim. The paper looks at problems:  (1)  Why  are  people  traumatized  and  afraid  in  facing  earthquakes  and  tsunamis?  (2)  Why are the younger generations not asking muslim scholars about the causes and effects of the earthquake and tsunami? Applying philological, historical, social and educational approaches, this article argues that  the  manuscript  of  the  earthquake  takwil  as  the  evidence  that  people  need  muslim  scholars  in explaining natural disaster. muslim scholars teach the students in surau about the cause of the earthquake and  its  takwil.  Earthquakes  and  tsunamis  have  long  been  studied  by  Minangkabau  muslim  scholars. Therefore,  it  needs  attention  and  reinforcement  of  knowledge  for  Muslim  scholars  of  West  Sumatra now in accordance with the times in addressing natural phenomena such as earthquakes and tsunamis.DOI: 10.15408/insaniyat.v2i1.6587